СОДЕЙСТВИЕ ПЛАНИРОВАНИЮ, ОРИЕНТИРОВАННОМУ НА КОНКРЕТНЫЕ РЕЗУЛЬТАТЫ, В РАЗВИВАЮЩИХСЯ СТРАНАХ: ПРИМЕР МИНИСТЕРСТВА СЕЛЬСКОГО ХОЗЯЙСТВА И РАЗВИТИЯ СЕЛЬСКИХ РАЙОНОВ ВЬЕТНАМА - ФамНгок Ха; НгуенТхи Хонг Хай (Вопросы государственного и муниципального управления, 2020)
Over the past decade, there has been an increased use of results-based management in Vietnam and other countries, but little empirical research exists on resultsbased planning (RBP). This research empirically examines the impact of four organizational factors on the outcomes of RBP. Data were based on 177 respondents from the Ministry of Agricultural and Rural Development – one of the pioneering government agencies adopting RBP in Vietnam. This study finds that employee commitment and RBP-related training have a direct, positive, and strong effect on the outcomes of RBP, and leadership support and involvement, donor support indirectly affect RBP outcomes via employee commitment. This study contributes to the literature by offering empirical evidence of the role of organizational factors in implementing reforms such as RBP in the context of a developing country. Some recommendations for furthering such reforms are also made.